Remembering childhood: Do our memories and experiences influence our understanding of early childhood and our practice with young children? - Horsley, Karen; Penn, Helen (Management in education, 2014)
Students on the Early Childhood Studies degree programme at the University of East London were asked to reflect on their childhood memories and how these have shaped their understandings of early childhood and practices with young children. Students’ rich and varied accounts reflect the diversity of largely non-traditional students from countries on every continent. Recurrent themes persist, but what remains constant is that memories are inescapably grounded in the sociocultural contexts of the times and places in which students grew up; a world away from traditional, reductionist ‘ages and stages’ or milestones. Drawing on Rogoff, differences and cultural influences, in the UK and elsewhere, on childhood and practice are worth exploring in developing many possible interpretations of the requirements of working with children and families. Inter-disciplinary conversations may help to identify and unpick complex relationships between childhood memories and every day work with young children, in the various practice settings students encounter.